2020
DOI: 10.3390/ijerph17197295
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Anxiety and Depression among Pregnant Pakistani Women: Higher Rates, Different Vulnerability Characteristics, and the Role of Perceived Stress

Abstract: Anxiety and depression commonly co-occur during pregnancy and may increase risk of poor birth outcomes including preterm birth and low birth weight. Our understanding of rates, patterns, and predictors of comorbid anxiety and depression is hindered given the dearth of literature, particularly in low- and middle-income (LMI) countries. The aim of this study is (1) to explore the prevalence and patterns of comorbid antenatal anxiety and depressive symptoms in the mild-to-severe and moderate-to-severe categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(60 reference statements)
4
19
1
1
Order By: Relevance
“…increased the odds of CAD. This finding is in line with the studies conducted in Pakistan 13.5% [6], Spain (9.5%) [7], South Africa (7.6% early and 9.7% in late pregnancy) [9] and a meta-analysis conducted by Falah and coworkers (9.5%) [4]. On the other hand, this finding is higher than the study conducted in Singapore (5.0%) [5] and very much lower than the study in Turkey (47.6%) [7].…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…increased the odds of CAD. This finding is in line with the studies conducted in Pakistan 13.5% [6], Spain (9.5%) [7], South Africa (7.6% early and 9.7% in late pregnancy) [9] and a meta-analysis conducted by Falah and coworkers (9.5%) [4]. On the other hand, this finding is higher than the study conducted in Singapore (5.0%) [5] and very much lower than the study in Turkey (47.6%) [7].…”
Section: Plos Onesupporting
confidence: 93%
“…Thiagayson and associates also reported that 5% of Singaporean women had prenatal CAD [ 5 ]. Likewise, studies from Spain, Turkey and Pakistan also demonstrated that 9.5%, 47.6% and 13.5% of pregnant women encountered CAD respectively [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) Há evidências em outros estudos de que a pandemia por si só age como fator estressor e contribui para o sofrimento psicológico durante a gestação, sendo considerado um forte preditor de ansiedade comórbida e sintomas depressivos leves a graves. (28,29) Os conflitos familiares também foram citados como responsáveis pelo aumento do estresse nas gestantes. (10) Segundo estudo realizado com participantes de todos os estados brasileiros, em tempos de isolamento é comum a observação da ocorrência de algum estresse familiar, havendo relação significante com a quantidade de pessoas vivendo na casa.…”
Section: Resultsunclassified
“…Biological . Two studies used biological vulnerability in the context of maternal health: risk of comorbid anxiety and depression in pregnancy [ 31 ], and HIV positivity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%